Effect of Shoditha Hingu (Ferula Asafoetida Linn) Prayoga in the Management of Kastarthava (Primary Dysmenorrhoea) - A Case Report (AYUSHDHARA, 2022)
Dysmenorrhea is one of the leading gynaecological disorders affecting women irrespective of age, economic status and the nationality. Primary dysmenorrhoea being one among the two types of dysmenorrhoea can be correlated to Kastartava in Ayurveda. Though the direct reference is not available, it can be compared to Kastartava or Udvartini yonivyapad because of upward movement of the Vata-kapha dosha along with Arthava associated with severe pain. In the present study, a female student aged 18yrs attended the OPD of Sushrutha Ayurvedic Medical College and Hospital, Bengaluru with the complaints of primary dysmenorrhoea was managed with Hingu prayoga for 3 months based on the Ayurvedic principles of management that are described in the classics by Acharyas. Significant reduction in abdominal pain and back pain was observed. Reduction of pain was stable during the three months of intervention and no adverse effects were found either during or after the treatment